2011
DOI: 10.1159/000332845
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tumor Thickness in Melanocytic Skin Lesions: Comparison of Optical Coherence Tomography, 20-MHz Ultrasound and Histopathology

Abstract: Background: Accurate assessment of vertical tumor size is important for surgical treatment planning of melanocytic skin lesions. High-frequency ultrasound (HFUS) is frequently used for this purpose, but overestimation of tumor thickness is known as a problem especially in thin melanocytic lesions. Optical coherence tomography (OCT) as a new imaging technique might be a promising alternative. Objective: To evaluate the ability of OCT to accurately determine the vertical tumor thickness of melanocytic skin lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 43 publications
0
44
0
2
Order By: Relevance
“…in the diagnostics of nonmelanoma skin cancer, for the measurement of tumor thickness of melanocytic lesions, for the evaluation of epidermal changes after different topical treatments and in the assessment of psoriatic nail disorders [13,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…in the diagnostics of nonmelanoma skin cancer, for the measurement of tumor thickness of melanocytic lesions, for the evaluation of epidermal changes after different topical treatments and in the assessment of psoriatic nail disorders [13,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…OCT was used for monitoring non-surgical treatment (imiquimod) of lentigo maligna. [43][44][45] The results of these studies showed a good correlation between OCT and pathology. In OCT melanoma is characterized by marked architectural disarray and presence of vertical, icicle-shaped structures.…”
Section: Optical Coherence Tomographymentioning
confidence: 71%
“…Both HFU and OCT tend toward tumor depth overestimation compared to histopathological ex vivo tumor measurement. 45 …”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The OCT has an optical resolution of [3][4][5][6][7][8][9][10][11][12][13][14][15] mm and can image up to 1 mm in depth (Kardynal and Olszewska, 2014). Hinz et al have shown that OCT has a stronger correlation with histopathology than HFU (Spearmen correlation, r = 0.734) (Hinz et al, 2011). They compared the tumor thickness of 26 melanocytic lesions measured from histopathology to OCT and HFU.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The median tumor thickness on histopathology was 0.25 mm while OCT and HFU were 0.31 mm and 0.44 mm, respectively. The concluded that OCT provides more accurate tumour depth than HFU that is frequently used for surgical planning for cutaneous melanocytic lesions (Hinz et al, 2011). OCT may have a lower resolution compared to RCM but it can provide realtime imaging to detect gross alteration in skin structure that can be easily correlated to conventional histopathology (Figure 1.5).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%